Detection of first- and second-order coherent motion in blindsight. - Pavan, A; Alexander, I; Campana, G; Cowey, A (2011)
Blindsight patients can detect fast moving stimuli presented within their blind field even when they deny any phenomenal visual experience. Although mounting evidence suggests the presence of different mechanisms and separate neural substrates underlying the processing of first-order (luminance-defined) and second-order (contrast-defined) motion, the perception of second-order motion in blindsight has scarcely been explored. In the present study, we investigated whether two blindsighted patients (GY and MS) can detect a variety of first- and second-order moving stimuli, and by using repetitive transcranial magnetic stimulation (rTMS), we assessed the role of V5/MT(+) and V3(+) in coherent motion processing. The hemianopes and four control subjects performed a two-interval forced-choice task in which they judged whether a pattern of coherently moving first-order or second-order textured squares moved in the first or second interval. They were not asked to report the direction of motion because neither of them could do so better than expected by chance. The results showed that MS, who has extensive destruction of the ventral cortical visual pathway as well as his V1 lesion, could not process second-order motion at all, whereas GY could perform second-order tasks but only at high-contrast modulation. This may have introduced first-order components in second-order moving stimuli and provided artifactual cues to motion. Moreover, rTMS delivered over area V5/MT(+) impaired detection of both first- and second-order motion in undamaged control subjects, whereas rTMS over V3(+) did not impair their performance in any of the stimuli employed. On the other hand, rTMS over V3(+) did impair GY's detection of first-order motion and high-contrast second-order moving textured squares that are likely to contain artifactual luminance cues. rTMS over V5/MT(+) impaired first-order motion detection in MS. Overall, the results suggest that neither of the blindsight patients can detect artifact-free second-order motion.